2018
DOI: 10.1002/ece3.4112
|View full text |Cite
|
Sign up to set email alerts
|

The combination of arbuscular mycorrhizal fungi inoculation (Glomus versiforme) and 28‐homobrassinolide spraying intervals improves growth by enhancing photosynthesis, nutrient absorption, and antioxidant system in cucumber (Cucumis sativus L.) under salinity

Abstract: Salinity is one of the major obstacles in the agriculture industry causing huge losses in productivity. Several strategies such as plant growth regulators with arbuscular mycorrhizal fungi (AMF) have been used to decrease the negative effects of salt stress. In our experiment, 28‐homobrassinolide (HBL) with spraying intervals was combined with AMF (Glomus versiforme) in cucumber cultivars Jinyou 1# (salt sensitive) and (Changchun mici, in short, CCMC, salt tolerant) under NaCl (100 mmol/L). Studies have docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…Consequently, AMF remarkably alters the source-sink relationships by facilitating the exchange of carbohydrates and mineral nutrients. [38,39] hypothesize that AM symbiosis can dramatically increase the gas exchange capacity of the cucumber plants probably by maintaining stomatal opening, reducing stomatal resistance and increasing the transpiration fluxes, and stimulating the photosynthetic traits ultimately causing the improvement of the biomass production of cucumber plants. The results suggest that the GS-AM association is more effective at augmenting plant biomass and crop phenology.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, AMF remarkably alters the source-sink relationships by facilitating the exchange of carbohydrates and mineral nutrients. [38,39] hypothesize that AM symbiosis can dramatically increase the gas exchange capacity of the cucumber plants probably by maintaining stomatal opening, reducing stomatal resistance and increasing the transpiration fluxes, and stimulating the photosynthetic traits ultimately causing the improvement of the biomass production of cucumber plants. The results suggest that the GS-AM association is more effective at augmenting plant biomass and crop phenology.…”
Section: Discussionmentioning
confidence: 99%
“… Family of host plant Host plant Fungus species Observed response Reference Solanaceae Lycopersicon esculentum L. Glomus mosseae Increased dry matter and leaf area, enhance enzyme activity Huang et al (2010) Solanaceae Lycopersicon esculentum L. Glomus intraradices, Glomus mosseae, Glomus aggregatum, Glomus clarum, Glomus monosporus, Glomus deserticola, Glomus brasilianum, Glomus etunicatum, Gigaspora margarita Increased plant growth, fresh stem weight, enhanced chlorophyll a and b content Demir et al (2011) Solanaceae Lycopersicon esculentum L . Glomus fasciculatum Improved P, phosphatase enzyme activity and reduced pH Sivakumar et al (2019) Solanaceae Capsicum annuum L. Glomus intraradices Improved root and shoot biomass, leaf area and cell membrane integrity Beltrano et al (2013) Solanaceae Capsicum annuum L. Glomus clarum Regulation of ions (K, Mg, Ca, Zn, Na) uptake, increased nutrient uptake and growth Altuntas et al (2016) Solanaceae Solanum melogena Glomus deserticola Enhanced growth and aggressiveness colonization in roots Mohammad and Mittra (2013) Amaryllidaceae Allium cepa L. Glomus fasciculatum Increased plant height, fresh weight and dry weight and reduced electrical conductivity Suhail and Mahdi (2013) Cucurbitaceae Citrullus lanatus L. Funneliformis mosseae Improved photosynthetic activity, elemental and water uptake Ye et al (2019) Cucurbitaceae Cucumis sativus L. Glomus versiforme Enhanced growth, improved photosynthesis and growth and reduced Na toxicity Ahmad et al (2018) Cucurbitaceae Cucumis sativus L. Glomus etunicatum,...…”
Section: Salinity Tolerance By Am Inoculation In Vegetablesmentioning
confidence: 99%
“…Mycorrhizal plants are more adaptable under adverse conditions such as drought and saline.The activity of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in the body is signicantly improved, which can slow down the oxidative damage of plants and enhance drought resistance. 37,38 The results of this study showed that the inoculated AMF mainly increased the enzyme activities (SOD, POD, CAT) to eliminate the accumulation of reactive oxygen species caused by drought stress, thereby reducing the damage caused by cell membrane lipid peroxidation. Studies have shown that inoculation can increase the CAT activity of Caragana korshinskii Kom.…”
Section: Discussionmentioning
confidence: 76%